Quantification of seismic performance factors of self-centered y-shaped braced frames. (July 2022) - Shahiditabar, Akbar; Moharrami, Hamid; Snijder, H.H.
Abstract: In this study, the methodology recommended by FEMA P695 is employed to evaluate the seismic performance of the self-centered y-shaped (SCY) braced frames. To apply this methodology to the system of interest, twenty archetype models are deigned. The collapse safety of the archetype models is then evaluated through incremental dynamic analyses (IDA) and pushover analyses. The results show that the secondary stiffness and length of the self-centering (SC) element are the key parameters which influence the overall behavior of the SCY braced frame. By increasing the length of the SC element, the effect of the SC element on the overall behavior of the SCY braced frame increases and this system shows greater initial elastic stiffness. Also, the extent of the SC capability of the proposed system depends on the length and the secondary stiffness of the SC element. To make the system of interest show fully SC behavior and to remove the residual displacement, increasing the length of the SC element as well as decreasing the secondary stiffness of the SC element are suggested. By decreasing the secondary stiffness of the SC element, the system over-strength factor decreases. For inclusion of the system of interest in the design code, the values of the response modification factor R and the system over-strength factor Ω0 are proposed to be 7 and 2 respectively. Highlights: The features of self-centered y-shaped (SCY) braced frames are studied. The methodology of FEMA P695 is employed to quantify the response modification factor R and the over-strength factor Ω0 . To make the system of interest show fully SC behavior increasing the length of the SC element as well as decreasing the secondary stiffness of the SC element are suggested. For inclusion of the system of interest in the design code the values of R and Ω0 are proposed to be 7 and 2 respectively.